Orientasi Kewirausahaan terhadap Keunggulan Bersaing dan Kinerja UMKM - Nst, Alfazrin; Siregar, Musannip Efendi; Pitriyani, Pitriyani (Fakultas Ekonomi Universitas Samudra, 2023)
The study aims to analyze the effect of entrepreneurial orientation on competitive advantage and the performance of SMEs. This research was conducted on clothing retail store owners in the Labuhanbatu Regency area. The sample used was 130 respondents using non-probability methods in the form of incidental and purposive sampling. In this study using normality test techniques and path analysis with the help of the Amos software application. The results of this study found that entrepreneurial orientation proved to have a positive and significant effect on competitive advantage; entrepreneurial orientation is proven to have a positive and significant effect on the performance of MSMEs; as well as, competitive advantage has proven to have a positive and significant effect on performance of MSME.